2004
DOI: 10.2144/04375pt03
|View full text |Cite
|
Sign up to set email alerts
|

Quenching Accumulation of Toxic Galactose-1-Phosphate as a System to Select Disruption of Protein-Protein Interactions in Vivo

Abstract: The reverse two-hybrid system has been developed to readily identify molecules or mutations that can disrupt protein-protein interactions in vivo. This system is generally based on the interaction-dependent activation of a reporter gene, whose product inhibits the growth of the engineered yeast cell. Thus, disruption of the interaction between the hybrid proteins can be positively selected because, by reducing the expression of the negative marker gene, it allows cell growth. Although several counter-selectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…(7) Reverse two‐hybrid system is an upside‐down version of Y2H, in which disruption of the bait–prey interaction decreases the expression of a counter‐selectable reporter gene, such as URA3, CYH2 and GAL1, and allows cell growth under selective conditions. This method facilitates the detection of dissociation of PPIs, and the selection of small‐molecule inhibitors against PPIs that could be developed as therapeutic agents …”
Section: Genetic Methodsmentioning
confidence: 99%
“…(7) Reverse two‐hybrid system is an upside‐down version of Y2H, in which disruption of the bait–prey interaction decreases the expression of a counter‐selectable reporter gene, such as URA3, CYH2 and GAL1, and allows cell growth under selective conditions. This method facilitates the detection of dissociation of PPIs, and the selection of small‐molecule inhibitors against PPIs that could be developed as therapeutic agents …”
Section: Genetic Methodsmentioning
confidence: 99%
“…The actions of GALK1 and GALT maintain the level of galactose-1-phosphate. The increase of galactose-1-phosphate, by an abnormal metabolic pathway, may cause various problems, as galactose-1-phosphate is thought to be a toxic metabolite [ 18 ]. Classic galactosemia is a representative disease of an accumulation of galactose-1-phosphate, by GALT deficiency, which is known to be the most common cause of galactosemia [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a GAL7 null background, GAL1 expression causes accumulation of galactose-1-phosphate, which eventually kills yeast. Pilot assays (including a pilot screening) have shown that this system could be used to detect small-molecule inhibitors of protein interactions, with a good sensitivity [36]. In contrast with URA3 or CYH2 reporters, this GAL1 system does not necessitate the use of a small molecule to achieve toxicity.…”
Section: Reverse Y2h Methodsmentioning
confidence: 99%